Avaliação da possível participação do NGF na patologia do megaesôfago induzido pela infecção pelo Trypanosoma cruzi - Jacqueline Garcia Duarte (2016)
Chagasic megaesophagus is one of major digestive complications of chronic Chagas' disease. It is believed that it develops due to the intense process of denervation, which in turn is due to the parasite infection and local inflammation. Knowing the role of NGF in the cross-talk between the immune system and the nervous system, its neurotrophic and pro-inflammatory properties, this study aimed to evaluate its participation in the pathology of chagasic megaesophagus. For this we analyzed esophageal samples from 12 infected individuals, six of them without megaesophagus or any symptoms of digestive disease and 6 with megaesophagus. The samples were subjected to immunohistochemistry with anti-NGF and anti-TrkA (NGF receptor). The results showed immunoreactivity for NGF and TrkA in the epithelium, eosinophils and mast cells and only for TrkA in inner muscle layer and neurons in the esophagus. In infected individuals without megaesophagus it demonstrated significant increased immunoreactivity for NGF in mast cells and increased immunoreactivity for TrkA in the epithelium, inner muscle layer and mast cells of inner muscle layer. In addition, negative correlation was seen between the number of neurons and the number of eosinophils and mast cells immunoreactive for NGF in the myenteric plexus. In infected individuals with megaesophagus was seen significant increase in immunoreactivity for NGF and TrkA in the epithelium, eosinophils and mast cells, and significant increase only for TrkA in the inner muscle layer. From these data, we suggest that increased immunoreactivity for NGF and TrkA in the esophagus of individuals infected with T. cruzi may be related to inflammation and also with the parasite infection.